Cloud-scale ISM structure and star formation in M51 - Leroy, Adam K.; Kruijssen, Diederik; Bigiel, Frank; Chevance, Mélanie (The astrophysical journal, 2017)
We compare the structure of molecular gas at 40 pc resolution to the ability of gas to form stars across the disk of the spiral galaxy M51. We break the PAWS survey into 370 pc and 1.1 kpc resolution elements, and within each we estimate the molecular gas depletion time ( ##IMG## [http://ej.iop.org/images/0004-637X/846/1/71/apjaa7fefieqn1.gif] $τ _\mathrmDep^\mathrmmol$ ), the star-formation efficiency per free-fall time ( ##IMG## [http://ej.iop.org/images/0004-637X/846/1/71/apjaa7fefieqn2.gif] $ε _\mathrmff$ ), and the mass-weighted cloud-scale (40 pc) properties of the molecular gas: surface density, Σ, line width, σ , and ##IMG## [http://ej.iop.org/images/0004-637X/846/1/71/apjaa7fefieqn3.gif]
Gesehen am 18.10.2017